Peran Self-Congruity dalam Memediasi Pengaruh Fashion Involvement terhadap Purchase Intention Produk Fashion : Studi pada UMKM Fashion di Kota Denpasar - Ni Luh Komang Tri Wulandari; Ni Made Asti Aksari (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Purchase intention is an important factor in determining sales performance and business sustainability because it reflects consumers’ tendency to purchase a product or service. This study was conducted among consumers of fashion micro, small, and medium enterprises (MSMEs) in Denpasar City, where fluctuations in the number of MSMEs indicate that consumers’ purchase intention has not been entirely stable. The study aimed to analyze the role of self-congruity in mediating the effect of fashion involvement on purchase intention toward fashion products. A quantitative approach with an associative research design was employed, involving 120 respondents. Data were analyzed using research instrument testing, descriptive analysis, and inferential analysis. The findings showed that fashion involvement had a positive and significant effect on both purchase intention and self-congruity. Self-congruity also had a positive and significant effect on purchase intention. Furthermore, self-congruity partially mediated the effect of fashion involvement on purchase intention among consumers of fashion MSMEs in Denpasar City. These findings contribute to consumer behavior literature and suggest that fashion MSMEs should strengthen consumer fashion involvement and align product images with consumers’ self-concepts to increase purchase intention.